Local sheet thickening by in-plane swaging. (December 2016) - Wernicke, S.; Sieczkarek, P.; Martins, P.A.F.; Tekkaya, A.E.
Abstract: This paper presents a new sheet-bulk forming process to locally pile-up material in thin sheets for subsequent forming or joining operations. An analytical solution is proposed for explaining the influence of the major process parameters, estimating the thickening of the pile-up material and determining the normal and thrust forces applied by the tools. The approach is built upon the slip-line field theory under plane strain assumptions and results are compared against finite element predictions and experimental results using Aluminium EN AW-1050A (EN 573-3) sheets with 3 mm thickness. The last part of the paper introduces a modified tool geometry that is able to control the pile-up material for subsequent mechanical fastening operations. Highlights: New sheet-bulk metal forming process for local sheet thickening with a cylindrical roll. Analytical model build upon the slip-line field theory to explain the deformation mechanics of the process, to estimate the thickening of the pile-up material and to calculate the normal and thrust forces. Identification of the process window and quantification of the deviations from plane strain deformation conditions. Modification of the tool to control the geometry of the piled-up material for subsequent local forming or joining operations.